(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Many women are familiar with the experience of spasmodic dysmenorrhoea, one of the commonest gynaecological conditions that affects the quality of life of many in their reproductive years. This condition manifested as painful menstruation, is the most frequently encountered gynaecological complaint and it can be included under Udavartha yonivyapat, caused by Apanavata vaigunya described in Ayurvedic classics. This situation not only has a significant effect on quality of life and personal health but also resulting in loss of work hours and depression. Scholastic backwardness and work absenteeism as a result of dysmenorrhoea is common nowadays. Most of the medical therapies for painful periods like analgesics, antispasmodics, NSAID, and anti-prostaglandins are having many side effects. Hormonal and surgical therapies are also not advisable to all type of patients, especially teenagers as it may harm their future reproductive capacity. Here comes the importance of Yoga, which provides good approach to treat primary dysmenorrhea. Yoga asanas helps in stretching muscles of pelvic cavity and increases the blood circulation to the pelvic organs and also helps to neutralize Apana vayu, which help in normal menstrual flow. The practice of Asanas has a beneficial impact on the whole body systems and helps in relaxation of both body and mind. This study is undertaken to find out the Yogasanas having pain relieving capacity in spasmodic dysmenorrhoea as it doesn’t cause any side effects but improve the quality of life. A thorough literary survey was done in Yogic classics especially Asanas for women’s health, Asanas for reproductive health and tried to compile the Asanas together having the pain relieving capacity in primary dysmenorrhoea.